Structured perioperative teaching (SPOT) among coronary artery bypass surgery (CABS) patients and cognitive, physical and psychosocial responses - So, Iris Chua
With scientific advancement in operative technology, nurses face the challenge of caring for clients undergoing such procedures as coronary artery bypass graft surgery. Care would include providing effective perioperative teaching with the goal of optimizing recovery. It is in this setting that an interest to develop a perioperative teaching tool called "Structured Perioperative Teaching (SPOT) for Coronary Arteru Bypass Surgery (CABS): arose.This research sought to determine the effect of structured perioperative teaching (SPOT) for coronary artery bypass surgery (CABS) on the knowledge scores, physical symptoms and psychosocial responses of patients post operation. It also sought to answer if there are differences in knowledge scores, physical symptoms and psychosocial responses of patients who received structured perioperative teaching (SPOT) for CABS and those who received existing perioperative teaching.This study used a pretest posttest experimental design with a probability sampling and random assignment. The sample size was thirty nine. Twenty were in the study goup and nineteen were in the control group. The structred perioperative teaching (SPOT) for CABS is an instructional tool that rendered cognitive information on preoperative and postoperative preparations for coronary artery bypass graft surgery. This was given to the study group preoperatively for 30 minutes and postoperatively for another 30 minutes.The subjects in the research study were predominantly male (81). Most were married (78.6) belonging to the 50-60 year old bracket (42.9) with a mean age of 59.4 years old. Majority have reached college level of education (64.3) and are still employed (69) at the time of data gathering.On analysis using paired t-test present at 0.05 level of significance, the study group scored a significant increase in knowledge scores (p=0.00012), had significantly lesser postoperative physical symptoms (p=0.00017) as compared to the control group and showed a considerable improvement in psychosocial outcomes (p=0.000463).The control group scored a non-significant increased in knowledge scores (p=0.0722) although the change was in the desired direction. There were more reported postoperative symptoms (p=0.00039) as compared to the study group. The psychosocial outcomes did not register a dramatic change in outlook in the control group although the change was also in the desired direction (p=0.161818).Structured perioperative teaching (SPOT) for CABS as an intervention was found to be beneficial in terms of increase in knowledge, decreased physical symptoms and improved psychosocial outcomes postoperatively. Patients who received structured perioperative teaching (SPOT) for CABS fared better than those who received existing perioperative teaching in terms of significant increase in knowledge scores, significantly lesser postoperative physical symptoms and considerable improvement in psychosocial responses.